Beyond Quota, Towards Women’s Representation In Indonesia: Quo Vadis? - Hanadia Pasca Yurista (lmu Administrasi Publik, FISIP, Universitas Sriwijaya, 2020)
This paper scrutinizes the effect of gender quota on women’s representation in the political landscape of Indonesia. By using the institutional analysis approach, the logic behind lethargic increases, even though such quota has failed to meet in Indonesia, is highlighted in the paper. This study further discusses the complex roles of various political and non-political actors that later affect the representation of women, including the political party, elected government and legislatures, and Commission for General Election (KPU). The institutional shift of gender quota implementation in Indonesian politics creates a tendency of disorientation of the main purpose of creating gender quota. As regulatory changes on the gender quota since its first implementation, this study examines the journey of quota and women representation in Indonesia which include the case of underrepresentation of women in politics and the controversy of women policy, as part of the initial virtue of implementing gender quota.